Coagulation in the HIV-positive pregnant patient: A thromboelastographic study - Mayeza, Slindile (Department of Anaesthesia and Perioperative Medicine, 2020)
Human immunodeficiency virus (HIV)infection is associated with haematological changes, including thrombocytopaenia. Pregnancy induces a hypercoagulable state. There are limited data on the coagulation status of women with term pregnancy and HIV receiving anti-retroviral medication. Regional anaesthesia is the technique of choice for caesarean section, and is contraindicated in a hypo-coagulable state. We therefore investigated the coagulation status of term pregnant women with HIV, presenting for elective caesarean section(CS). This was a single-centre cross-sectional observational study, using thromboelastography, comparing the coagulation status of HIV negative and -positive women with no other comorbidities, in pregnancy at term. A blood sample was taken immediately prior to spinal anaesthesia, and thromboelastography was performed within 4 minutes. In addition, platelet count, haemoglobin, and fibrinogen level were measured. Blood samples were obtained from 75 patients. There were no between-group differences in obstetric and demographic data, and no difference in platelet count. The mean (SD) fibrinogen level was higher in HIV positive women (3.9 [1.5] vs 3.5 [0.7] g/L) respectively, p=0.04. There were no significant differences in the r-time, alpha-angle, k-time, MA, or LY-30. The results of this thromboelastography study show that in asymptomatic HIV positive pregnant patients on anti-retroviral treatment, there are no significant differences in coagulation parameters when compared with HIV negative patients. This suggests that routine assessment of coagulation is unnecessary before spinal anaesthesia in patients without other co-morbidities. Further studies could demonstrate the incidence of abnormalities in coagulation or platelet function in patients with AIDS defining disease or HIV positive patients with other co-morbidities.